Decoding the Special Purpose Acquisition Companies: A New Frontier in Tech Start-Up Financing - Tan, David; Disemadi, Hari Sutra; Sudirman, Lu (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
The emergence of SPAC has democratized participation in the burgeoning equity market. Capital raised during a SPAC's Initial Public Offering (IPO) is typically held in escrow identifies a suitable acquisition or merger target. This study explores the concept of SPACs, their operational mechanisms, their appeal to tech startups, and their presence in Asia, with a specific focus on the Indonesian jurisdiction. The study also aims to identify the potential risks SPACs may pose to the equity market to inform more effective regulation. Employing normative legal research and prioritizing secondary data, the findings of this paper indicate that SPACs have evolved from a niche option to a significant facilitator for private enterprises seeking to enter public markets through an IPO. The study further reveals that, despite the risks associated with SPACs and their current unpreparedness for IPOs in Indonesia, lessons from foreign experiences could guide the development and implementation of domestic regulations. While SPACs have demonstrated their value and promise to become a significant market force, calls for swift regulatory action should balance the benefits of SPACs against the need for thoughtful regulation, presenting an opportunity to reconsider existing IPO regulations.DOI: https://doi.org/10.22304/pjih.v11n1.a5